Development of a smart solar photovoltaic inverter - Tan, Sheng Hui (Nanyang Technological University, 2020)
Solar energy is the cleanest and an inexhaustible source of renewable energy sources. There is a continuous growth of demand for Solar PV systems over the decade and improving technologies that aim to enhance the efficiency of the PV system. The overall efficiency of the PV systems mainly depends on the efficiency of the Direct Current (DC) of solar modules to Alternating Current (AC) inverter conversion. The report aims to introduce the Development of a Smart Photovoltaic Inverter that helps to further improve the efficiency of the inverter yet at the same time produces a superior output voltage quality by using the T-type circuitry connection. The paper also discusses the sizing method of LC filter through analyzation of the output waveforms and kept within the specific requirements. Lastly, the transfer functions of the control block diagram will be formulated and implemented on a simulation platform, while considering the overall stability of the system when designing the PI controller using various test method.